Immunological weapons against acute myeloid leukaemia. - Galea-Lauri, J (2002)
A better understanding of the biology of malignant cells and of the host immune system together with dramatic advances in technology have led to the design of innovative immune-mediated approaches to control neoplastic clones, including various haematological malignancies. One of the major problems with conventional cancer therapies is their inability to eradicate residual cancer cells that are resistant to therapy, hence immune intervention might improve the clinical outcome of patients. This mini-review will focus mainly on immunological approaches to the therapy of acute myeloid leukaemia (AML), a subset of a much larger family of leukaemias. Immune-mediated approaches ranging from allogeneic lymphocyte transplants to cytokine therapy, immune-gene therapy and vaccination by dendritic-cell-based vaccines will be discussed.